Early-age creep of 3D printable mortar: Experiments and analytical modelling. (April 2023) - Chang, Ze; Liang, Minfei; Xu, Yading; Wan, Zhi; Schlangen, Erik; Šavija, Branko
Abstract: In this study, an experimental setup to characterize the early-age creep of 3D printable mortar was proposed. The testing protocol comprises quasi-static compressive loading-unloading cycles, with 180-s holding periods in between. An analytical model based on a double power law was used to predict creep compliance with hardening time and loading duration as inputs. Subsequently, this analytical model was validated by comparison to uniaxial compression tests in which loading is increased incrementally, i.e., in steps, showing a good quantitative agreement. Minor differences between the two results were noted, most notably at the beginning of the test. This is because the determination of creep compliance for 3D printable mortar at fresh stage depends on the load level. In the end, the volumetric strain of tested samples from uniaxial compressive test is used to explain why the compressive loading affects the creep deformation.